Coping with cold: Sorghum cold stress from germination to maturity. Issue 6 (28th September 2021) - Casto, Anna L.; Murphy, Katherine M.; Gehan, Malia A.
Abstract: Sorghum [ Sorghum bicolor (L.) Moench] is an important crop that is highly drought tolerant but susceptible to low temperatures. Many studies have begun to explore the genetic basis of variation in chilling sensitivity in the sorghum germplasm in an effort to improve sorghum's chilling tolerance. However, differences in genetic maps and updates to the sorghum reference genome have made comparing studies of chilling in sorghum challenging. Here, we review the current state of research on chilling tolerance and susceptibility in sorghum during germination and emergence, vegetative growth, and reproduction and harvest stages. Using the most recent sorghum reference genome (v3.1), we have standardized the locations of quantitative trait loci and marker‐trait associations for chilling tolerance traits across the literature. This revealed substantial overlap between quantitative trait loci/marker‐trait associations identified for similar traits across studies of different sorghum populations. Chromosomes 2, 3, and 6 contained particularly concentrated regions of markers associated with chilling tolerance traits. Although many studies have uncovered genetic variation for chilling responses in the sorghum germplasm, follow‐up studies are needed to confirm and characterize the molecular mechanisms responsible for variation in chilling tolerance in sorghum. We discuss potential molecular mechanisms for cold stress tolerance based on agreements between studies and address the challenges and opportunities for increasing chilling tolerance in sorghum and other next‐generation crops. Core Ideas: Review of sorghum chilling tolerance literature from germination to maturity. Coordinates of chilling tolerance loci are standardized and regions of high overlap between genetic markers are highlighted. Molecular mechanisms underlying chilling tolerance and susceptibility are discussed.